Silver melamine thin film as a flexible platform for SERS analysis. Issue 15 (13th April 2021) - Nenashkina, Anastasia; Koltsov, Semyon; Orlova, Olga Yu.; Nikitina, Anna A.; Kirilenko, Demid A.; Andreeva, Daria V.; Blanco-Formoso, Maria; Pazos-Perez, Nicolas; Alvarez-Puebla, Ramon; Skorb, Ekaterina V.
Abstract : The new SERS detection platform is applicable for the quick and easy formation of sensing devices for food, agriculture, and environmental science. Abstract : New SERS detection platforms are required for the quick and easy preparation of sensing devices for food, agriculture, and environmental science. For quantitative sensing, it is important that a sensing material, in addition to efficient sensing, provides extraction and concentration of the target molecules such as toxic pesticides or healthy vitamins. We design such films adopting the Liesegang rings formation process that includes the reaction–diffusion of silver nitrate and melamine followed by the precipitation of different intermediates and their reduction by light in a pectin medium. Surprisingly, we find that the presence of melamine provides an excellent substrate for the extraction of pollutants at the solid-liquid interface giving rise to a powerful but easy and fast method for the quantification of fruits' quality. The complex silver and melamine containing films show high sensitivity even at relatively low silver concentrations.